2008
DOI: 10.4049/jimmunol.181.8.5738
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Type V Collagen Humoral Immunity in Lung Transplant Primary Graft Dysfunction

Abstract: Primary graft dysfunction (PGD) is a major complication following lung transplantation. We reported that anti-type V collagen (col(V)) T cell immunity was strongly associated with PGD. However, the role of preformed anti-col(V) Abs and their potential target in PGD are unknown. Col(V) immune serum, purified IgG or B cells from col(V) immune rats were transferred to WKY rat lung isograft recipients followed by assessments of lung pathology, cytokines, and PaO2/FiO2, an index of lung dysfunction in PGD. Immune s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
112
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 103 publications
(116 citation statements)
references
References 34 publications
(76 reference statements)
4
112
0
Order By: Relevance
“…found on the apical surface of airway epithelium, it is not secreted by such cells into the extracellular milieu (26). We observed robust expression of ␣1(V) in response to IL-17 and TGF-␤ treatment, which is the same ␣-chain recognized as the antigen.…”
Section: L409 Il-17 Mediated Col(v) Overexpression and Emtmentioning
confidence: 59%
See 1 more Smart Citation
“…found on the apical surface of airway epithelium, it is not secreted by such cells into the extracellular milieu (26). We observed robust expression of ␣1(V) in response to IL-17 and TGF-␤ treatment, which is the same ␣-chain recognized as the antigen.…”
Section: L409 Il-17 Mediated Col(v) Overexpression and Emtmentioning
confidence: 59%
“…Col(V), which can be considered a cryptic antigen, is normally intercalated within fibrils of col(I) (34). As such, col(V) is expressed at low levels in perivascular interstitial spaces and on the apical, but not basolateral, surfaces of airway epithelial cells (26). We have previously reported de novo generation of antibodies to col(V) in patients with lung transplants with OB (49) and that this was IL-17 dependent (14).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, mutations in the genes encoding either ␣1(V) or ␣2(V) chains result in the human connective tissue disorder classic Ehlers-Danlos syndrome, characterized by collagen I fibrils of abnormal shapes and diameters and deficient tensile strength (7,8). More recently, it has been demonstrated that anti-col(V) autoimmune responses can underlie chronic lung transplant rejection in both humans (9) and animal models (10) and that pre-transplant col(V)-specific autoimmunity is also a significant risk factor for primary graft dysfunction, the leading cause of early morbidity and mortality after lung transplantation (11,12). Col(V) autoimmunity has also been identified as a consistent feature in both late stage human coronary artery disease and a mouse model of atherosclerosis (13).…”
Section: Collagen Type V (Col(v))mentioning
confidence: 99%
“…Antibodies to col(V) were detected in patients' plasma using a patented flow cytometry bead assay (ImmuneWorks, Indianapolis, IN, USA) [18]. A floating cut-off was determined by using serum from 66 adult, nonsmoking normal volunteers, following an immunogenicity white paper [19].…”
Section: Anti-col(v) Ab Detectionmentioning
confidence: 99%